Rotary Inverted Pendulum Control with Pole Placement - Fahmizal; Geonoky; Maghfiroh, Hari (Peneliti Teknologi Teknik Indonesia, 2023)
The inverted pendulums are multivariable and highly unstable dynamic systems. The inverted pendulum has been used to answer many modern control and control system designs because it has several problems relating to the system model of nonlinearity, difficulty, and inactivity. In this research, the main topic is the rotatory inverted pendulum. Circular path to eliminate the path that is on the pendulum that is traversed by the transversal path. In this paper, the Inverted Rotatory Pendulum is analyzed by state feedback which is adjusted by pole placement. The result of design selection in the system is very important to pay attention to the area where the pendulum will reach the point of agreement.